Implementation of Continuity of Care in New Born and Toddlers in the Era of the Covid 19 Pandemic In Napa Village, Angkola Selatan District, Tapanuli Selatan Regency - Harahap, Maryam Latifah; Rahmah Juliani Siregar; Fatimah; Elvi Suryani; Cut Khairunnisah Harahap; Ayu Ariana; Aisyah Siregar (IJCS: International Journal of Community Service, 2022)
Medium Indonesian face disaster non-nature national Covid-19 so that service maternal and neonatal health to be wrong one affected services impact good in a manner access nor quality. order mother and baby permanent could always get care continuous During period pandemic, then as power health especially midwife could conducted care sustainable midwifery (Continuity of care) on Mother and family. On period pandemic this power health must more innovative in carry out care to family , however permanent must notice protocol health related Covid-19 in give care on mother especially newborns (BBL) and ba lita. The goal to be achieved in activity this is for ensure that Mother accept all his upbringing from one midwife or team in practice, also for know the definition, benefits, implementation and for increase tkan number level more health good on newborns (BBL) to toddlers, healthy physical and grow as well as develop normally in the era pandemic C ovid-19. The method used with do surveys and interview for data collection, data analysis, data presentation , formulating discussion and next given communication, information and education (KIE) conducted with 2 method , that is online with use including applications SMS, zoom, WA and application other . And the direct way is to hold counseling by complying with health protocols.